2018
DOI: 10.18632/oncotarget.25748
|View full text |Cite
|
Sign up to set email alerts
|

Positive crosstalk between EGFR and the TF-PAR2 pathway mediates resistance to cisplatin and poor survival in cervical cancer

Abstract: Cisplatin-based chemoradiation is the standard treatment for cervical cancer, but chemosensitizing strategies are needed to improve patient survival. EGFR (Epidermal Growth Factor Receptor) is an oncogene overexpressed in cervical cancer that is involved in chemoresistance. Recent studies showed that EGFR upregulates multiple elements of the coagulation cascade, including tissue factor (TF) and the protease-activated receptors (PAR) 1 and 2. Moreover, many G protein-coupled receptors, including PARs, have been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 55 publications
0
40
0
Order By: Relevance
“…47 More recently, Hugo de Almeide et al showed that TF signaling drives a positive feedback loop in EGFRdependent cisplatin-resistant cervical cancer. 48 That is, the TF:FVIIa signaling complex activates PAR2, which then transactivates EGFR, one of the known regulators of TF and a promotor of chemoresistance. 48 Besides affecting the cell response to chemotherapy negatively, TF is known to sensitize neuroblastoma to doxorubicin.…”
Section: Regulation Of Tissue Factor Transcription and Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…47 More recently, Hugo de Almeide et al showed that TF signaling drives a positive feedback loop in EGFRdependent cisplatin-resistant cervical cancer. 48 That is, the TF:FVIIa signaling complex activates PAR2, which then transactivates EGFR, one of the known regulators of TF and a promotor of chemoresistance. 48 Besides affecting the cell response to chemotherapy negatively, TF is known to sensitize neuroblastoma to doxorubicin.…”
Section: Regulation Of Tissue Factor Transcription and Activitymentioning
confidence: 99%
“…48 That is, the TF:FVIIa signaling complex activates PAR2, which then transactivates EGFR, one of the known regulators of TF and a promotor of chemoresistance. 48 Besides affecting the cell response to chemotherapy negatively, TF is known to sensitize neuroblastoma to doxorubicin. 49 Taken together, chemotherapy-induced cellular responses including induction of apoptosis, induction of cell cycle arrest, and increased PDI localization on the cell surface may all partly explain the procoagulant phenotype observed in chemotherapy-treated cancer patients.…”
Section: Regulation Of Tissue Factor Transcription and Activitymentioning
confidence: 99%
“…Several examples of cancer-related signaling events mediated by coagulation receptors have been characterized and implicated in various aspects of disease pathogenesis, ranging from metastasis and angiogenesis to drug resistance. 15,19,25 It is presently unclear whether, and to what extent, the clinically used pharmacological thromboprophylaxis and anticoagulation measures meaningfully impact cellular events associated with cancer and whether their modification may impact patient survival. 3,26,27 From a mechanistic standpoint, it is reasonable to consider CAT as an aftermath of dysregulated expression and/or function of canonical effector mechanisms within the hemostatic system.…”
mentioning
confidence: 99%
“…Therefore, the use of drugs to suppress PGE 2 synthesis may reduce the risk of cervical lesions. In the treatment of cervical cancer, patients with upregulated expression of COX-2 have a worse prognosis than patients who do not, irrespective of whether radiotherapy or chemotherapy is administered (47,48). Therefore, COX-2 inhibitors, such as ibuprofen and aspirin, may reduce the risk of cervical cancer recurrence (29).…”
Section: Discussionmentioning
confidence: 99%